REORIENTASI PENDIDIKAN KEWARGANEGARAAN DI PERGURUAN TINGGI SEBAGAI WAHANA SISTEMIK PENINGKATAN INTEGRITAS NASIONAL (Satu Tinjauan Filsafat Pendidikan) - Hakim, Alif Lukmanul (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2007)
The main purpose of this article is to describe in general and briefly the concept of citizenship education for all can be used as medium to increase national integrity of the Indonesian society through the reorientation effort viewed from the Educational philosophy analysis. The factual reality showed to us, how the national integrity becomes the crucial problem ensuring the unity of nation in the constructive form, so the effort to make it can be implemented is one of the obligations and rightful authorities of citizen. Bases on the purpose of this article, can be concluded that citizenship education for all is the most significantly and concrete effort to increasing the integrity of nation based on the civic intelligence of the nation progress, and the creation space for civic participation via learning interactions participative, democratically, civilize emancipative, and coexistent.